Rapidity dependence of antideuteron coalescence in pp collisions at √s=13 TeV with ALICE - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Menzel, Marius; Nath, Abhishek; et al. (Physics letters, 2024)
The production yields of antideuterons and antiprotons are measured in pp collisions at a center-of-mass energy of s=13 TeV, as a function of transverse momentum (pT) and rapidity (y), for the first time rapidity-differentially up to |y|=0.7. The measured spectra are used to study the pT and rapidity dependence of the coalescence parameter B2, which quantifies the coalescence probability of antideuterons. The pT and rapidity dependence of the obtained B2 is extrapolated for pT>1.7 GeV/c and |y|>0.7 using the phenomenological antideuteron production model implemented in Pythia 8.3 as well as a baryon coalescence afterburner model based on EPOS 3. Such measurements are of interest to the astrophysics community, since they can be used for the calculation of the flux of antinuclei from cosmic rays, in combination with coalescence models.
ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, N.A. Grunwald, M.W. Menzel, A. Nath, Y. Pachmayer, K. Reyers, R. Schicker, F. Schlepper, J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone, B. Zhang und 1055 weitere
Gesehen am 09.10.2025